2022
DOI: 10.1016/j.heliyon.2022.e08835
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir for pregnancy: A systematic review of antiviral therapy for COVID-19

Abstract: The use of remdesivir for pregnant patients with coronavirus disease 2019 (COVID-19) showed conflicting results in prior studies. We aimed to systematically review its efficacy and safety for this population from the existing literature. Methods: On July 26, 2021, registries (ClinicalTrials.gov) and databases (MEDLINE, ScienceDirect, Cochrane Library, JSTOR, DOAJ, and medRxiv) were systematically searched for research articles investigating remdesivir use in pregnant people with COVID-19. Clinical outcome, hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
2
16
0
2
Order By: Relevance
“…46 Although the efficacy and safety profile of remdesivir among pregnant women remains inconclusive, a recent systematic review reporting nine case reports and case series demonstrated clinical recovery after remdesivir treatments. 47 Remdesivir improved the clinical condition of pregnant patients with COVID-19, especially those with a better clinical status at baseline and who received treatment earlier in the course of the disease. 47 , 48 The current WHO guidelines updates the use of remdesivir for patients with nonsevere COVID-19: its use reduces hospital admission in the highest risk group, although with little or no impact on mortality.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…46 Although the efficacy and safety profile of remdesivir among pregnant women remains inconclusive, a recent systematic review reporting nine case reports and case series demonstrated clinical recovery after remdesivir treatments. 47 Remdesivir improved the clinical condition of pregnant patients with COVID-19, especially those with a better clinical status at baseline and who received treatment earlier in the course of the disease. 47 , 48 The current WHO guidelines updates the use of remdesivir for patients with nonsevere COVID-19: its use reduces hospital admission in the highest risk group, although with little or no impact on mortality.…”
Section: Discussionmentioning
confidence: 90%
“… 47 Remdesivir improved the clinical condition of pregnant patients with COVID-19, especially those with a better clinical status at baseline and who received treatment earlier in the course of the disease. 47 , 48 The current WHO guidelines updates the use of remdesivir for patients with nonsevere COVID-19: its use reduces hospital admission in the highest risk group, although with little or no impact on mortality. 49 Adverse reactions and transaminase enzyme levels should be followed after remdesivir administration; the most common adverse event following remdesivir treatment is transaminitis.…”
Section: Discussionmentioning
confidence: 90%
“…In the compassionate use program patients with severe COVID-19 treated with remdesivir showed good outcome but higher rate of preterm birth. It is unclear if this is related to the antiviral use or a complication of COVID-19[ 38 , 39 ]. This doubt was partially clarified in a study comparing pre-delivery and post-delivery treatment with remdesivir in which the rate of pre-term delivery was similar[ 40 ].…”
Section: Pico 19: What Is the Effect Of Remdesivir Treatment (I) On M...mentioning
confidence: 99%
“…Kehamilan dengan infeksi dapat menyebabkan terjadinya gawat janin dan persalinan prematur. Angka kematian pada wanita hamil akibat COVID-19 mencapai 25% dari populasi (Budi et al, 2022;Favilli et al, 2020;Juanita et al, 2021;Kundarto & Faizah, 2021). Hingga saat ini, pengetahuan tentang COVID-19 yang berhubungan dengan kehamilan dan janin masih terbatas dan belum ada rekomendasi yang dikeluarkan oleh WHO secara spesifik untuk penanganan COVID-19 pada kehamilan.…”
Section: Pendahuluanunclassified